Reverse Logistics Activities for Household E-Waste Management: A Review - Azlina Muhammad; Muhammad Zaly Shah Muhammad Hussein; Mohd Hafiz Zulfakar; Veera Pandiyan Kaliani Sundram (International Journal of Supply Chain Management, 2020)
Recently, with the advancement of technologies in all fields of life, the competition has increased among manufacturing companies and industries. Reverse logistics is one of the significant and well-known activities to improve the business processes from the point of origin to destination. Reverse logistics activities have implemented in different business operations in which one of the significant areas is household e-waste management. With the passage of time, different types of household products have been piling up and cause for environment and waste issues. In order to tackle these mounting waste issues, reverse logistics activities are promoting product recovery and strategies for e-waste management. This review points out the fundamental of reverse logistics and looks into the existing activities for e-waste management. The main objective of this paper is to highlight the recent growing concern to controlling rising global pollution by household waste. The added value of this paper is the exploration of reverse logistics filed for household e-waste management. Through extensive literature review, this paper concludes the gap and recent activities in the field. Through this review, a novel contribution has been drawn to highlight the extent to which reverse logistics activities have penetrated in household e-waste management.